Enhancing the Resilience of Microfinance Institutions and Programs: Lessons Learned from the Asian Financial Crisis - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1998)
The evidence from selected Asian countries shows that: * Microfinance on the whole has weathered the crisis well. The strongest of the microfinance systems in the region, the BRI unit system in Indonesia, has emerged from the crisis even stronger than before, characterized by a surge in savings deposits and continued excellent repayment performance. * Demand for microcredit has not increased; there are some cases, as in the BRI units, where it has declined; in other cases, as among some Grameen replicators in the Philippines, neither the demand for, nor the supply of, microcredit seem to be affected. The resilience of microfinance in crisis situations, just as in normal times, appears to be most strongly influenced by three major factors: * the institutional autonomy and self-reliance of MFIs in terms of internal resource mobilization and operational terms and conditions * negatively by financial repression, comprising interest rate regulation, a lack of legal forms for MFIs, and a preponderance of subsidized targeted program credit which in one form or the other has persisted in every country * positively by the deregulation of interest rates, institutional liberalization and the provision of appropriate legal forms for MFIs, accompanied by prudential regulation and effective supervision (the lack of which was a major factor in the downfall of the banking sector in the affected Asian countries).
Keywords: 330